The effect of herbal phytoextract on metabolic parameters of sows and piglets - A. A. Ivanovsky; N. A. Latushkina; E. Yu. Timkina (Аграрная наука Евро-Северо-Востока, 2021)
The purpose of the research was to study the effect of a phytocomplex containing herbal extracts of R. carthamoides, S. coronata, F. ulmaria on blood biochemistry of milking sows, the development and viability of piglets born by the time of weaning. For the experiment, the animals were divided into an experimental (Phytoadditive) and a control (SPK-2 compound feed) groups, 10 animals each. Phytoadditive in dry form was introduced into the diet of pigs of the experimental group during the sucking period (30 days) daily, once per head per day - 10 grams (individually). Before the beginning and at the end of the experiment, the blood of sows was examined for biochemical parameters. The multiplicity, the quality of the piglets born, the weight of the nest and one pig after birth and before weaning, as well as viability were determined. As the result, it was found that the concentration of the investigated extractives in the Phytoadditive was 13.5 g/kg, of which 10.5 g were ecdysteroids and 3.0 g of flavonoid rutin. Significant changes in the total protein content in the blood compared with the beginning of the experiment were noted in experimental pigs from 60.2±0.5 to 67.3±0.2 g/l (P <0.05) and in the control group from 61.0±0.2 to 66.1±0.1 g/l (P <0.05), the "Ca" content from 2.1±0.01 to 2.7±0.02 mmol/l (P <0.05) in the experimental group and from 2.0±0.01 to 2.5±0.02 mmol/l (P <0.05) in the control groups, while being within the normal range. The amount of albumin significantly increased only in the experimental group from 40.8±1.2 to 49.3±2.8 g/l (P <0.05), in the control from 42.2±2.1 to 46.0±1.5 g/l (P> 0.05). The number of piglets with low viability in the experimental group was 2 times less than in the control group. The viability of piglets in the experimental group by the time of weaning was 92.6 %, in the control ‒ 83.2 %.